Innovations in Elementary School Health Promotion Programs: An Integrative Review - Muhammad Hilmy As Shiddiq; Gunawan Gunawan; Hamsu Kadriyan; Baik Nilawati Astini; Ni Made Yeni Suranti (Indonesian Publication Center, 2025)
Elementary schools represent a strategic setting for instilling healthy behaviors early in life, as children are in a critical period of habit and character formation. Along with the evolution of educational practices, conventional health education methods have shifted toward more interactive, participatory, and holistic approaches. This study aims to explore and synthesize recent innovations and strategies in implementing health programs in elementary schools. An integrative review design was applied by analyzing 44 selected articles, including quantitative, qualitative, and experimental studies. The reviewed literature focuses on interventions related to physical health, mental health, and dental health among elementary school students. The findings identify four main clusters of program innovation: the use of creative media and gamification to enhance health knowledge, classroom-based mental health interventions such as deep breathing and mindfulness, the integration of physical education to address obesity prevention and character development, and comprehensive school health management that emphasizes the role of teachers and supportive school policies. The review concludes that health programs in elementary schools are shifting from one-way counseling toward more engaging and participatory interventions, with multidimensional approaches demonstrating greater effectiveness in improving student health outcomes.